2022
DOI: 10.58291/ijsecs.v1i2.51
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Using Augmented Reality on Students' Cognitive And Affective Aspects In Terms of Education Level

Abstract: Many studies related to the use of Augmented Reality (AR) in the learning process. However, not many researchers have studied the effect of using AR on affective and cognitive aspects in terms of education level. To uncover this problem, the researcher uses a systematic literature review (SLR) design. In this study, the SLR stage consisted of four stages (1) problem formulation; (2) literature search; (3) identification of the type of research; (4) information retrieval. The findings of this study reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In terms of affective aspects, the use of AR strengthens students' interest and motivation in mathematics. This is consistent with the findings of Runisah et al (2022), who observed that the motivation of secondary school students increased after using AR applications in mathematics learning. The use of AR applications can also reduce mathematics anxiety (Fitria, 2023;Saha et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of affective aspects, the use of AR strengthens students' interest and motivation in mathematics. This is consistent with the findings of Runisah et al (2022), who observed that the motivation of secondary school students increased after using AR applications in mathematics learning. The use of AR applications can also reduce mathematics anxiety (Fitria, 2023;Saha et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The analysis of studies indicates that the use of AR in mathematics learning has the greatest impact on students' cognitive development in secondary schools. Runisah et al (2022) also showed that the use of AR in mathematics learning can improve various cognitive aspects such as visual thinking skills, learning outcomes and concept understanding. In terms of affective aspects, the use of AR strengthens students' interest and motivation in mathematics.…”
Section: Discussionmentioning
confidence: 97%